The Effectiveness Of Animation Movie Through Retelling Technique To Improve The Students’ Speaking Ability - Iksan (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2018)
This research aims: (1) To find out whether or not the use of animation movie through retelling technique is effective to improve the students’ speaking ability and (2) to find out the students' motivation toward the use of animation movie in learning speaking. This research employed quasi experimental design. The population of this research was the eleventh grade students of SMA Negeri 18 Makassar in academic year 2017/2018. This research used cluster random sampling. The sample of this research consisted of 80 students that belong to two groups; 40 students in control group and 40 students in experimental group. The research data was collected by using speaking test through interview and questionnaire which were analyzed by descriptive and inferential statistic through SPSS version 21.00 for windows program. The students’ result of posttest of experimental group is significantly improved than the students’ result of posttest of control group by the mean score 71.22 > 57.81. The difference of both scores is statistically significant based on the t-test value at significant level 0.05 in which the probability value is lower than the significant level (0.00 < 0.05). The mean score of the students’ motivation is 85.55 and it is categorized as high motivation. It can be concluded that the use of animation movie through retelling technique is effective to improve the students’ speaking ability, and the students have a high motivation in learning speaking by using animation movie.